Fresno County Bar Association and Fresno County Women Lawyers Joint Luncheon with Betty Medsger - Watkins, Howard::::::::: (1986)
Mary Louise Frampton at lectern introducing keynote speaker Betty Medsger; seated: Catherine Taylor, Betty Medsger and Judy Soley on far right